Instructional materials: a platform to enhance cognitive skills and writing development - Muñoz Oyola, Jorge Enrique (Colombian Applied Linguistics Journal, 2010)
This paper describes the results of an action research project carried out with irst graders at a private coeducational school in Bogotá, Colombia. The purpose of the study was to account for children’s cognitive skills and writing development when using designed instructional materials based on the Structural Cognitive Modiiability model (SCM). The indings of the research suggest that children’s cognitive skills development evolves through a three-stage ongoing cycle. The indings also reveal that they become creative writers by recalling prior knowledge and integrating L1 and L2 elements. This study shows that mediation serves as a bridge between learners’ dificulties and understanding, highlights the use of L1 as a language acquisition facilitator.